Metal Markers - Dobla, Corta, Crea - "Metalizate" (2024)
This project arises from the need identified among Design students Industrial of the Antonio Nariño University, who expressed concerns about the selection and use of materials in the development of prototypes. The main objective is to create an autonomous learning kit for students of Industrial Design, which focuses on strengthening capabilities and knowledge about the use of metal (iron), as well as providing information on the techniques and use of tools used in material transformation processes.